2016
DOI: 10.1016/j.drugalcdep.2016.04.013
|View full text |Cite
|
Sign up to set email alerts
|

The effects of oral d-amphetamine on impulsivity in smoked and intranasal cocaine users

Abstract: BACKGROUND Effective treatments for cocaine use disorders remain elusive. Two factors that may be related to treatment failures are route of cocaine used and impulsivity. Smoked cocaine users are more likely to have poorer treatment outcomes compared to intranasal cocaine users. Further, cocaine users are impulsive and impulsivity is associated with poor treatment outcomes. While stimulants are used to treat Attention Deficit Hyperactivity Disorder (ADHD) and attenuate certain cocaine-related behaviors, few st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 121 publications
(152 reference statements)
0
12
0
Order By: Relevance
“…Several studies did include at least three tasks designed to measure different aspects of impulsivity 46,48,49,54 ; however, the tasks used in these studies differed substantially, precluding meaningful comparisons between them. This review illuminates the need for future studies to incorporate multiple tasks designed to measure different aspects of impulsivity, if more practical comparisons are to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies did include at least three tasks designed to measure different aspects of impulsivity 46,48,49,54 ; however, the tasks used in these studies differed substantially, precluding meaningful comparisons between them. This review illuminates the need for future studies to incorporate multiple tasks designed to measure different aspects of impulsivity, if more practical comparisons are to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…49,53,60 The remaining studies did not report the duration of washout periods [44][45][46][50][51][52]56 or used parallel-group designs. 48,59 The most widely used behavioural impulsivity tasks were the Stop-Signal Task, [49][50][51][52]55,60 Stop/Go Task/Stop Task, 28,46,47,54,57 Go/No-Go Task, 43,53,54 Delay Discounting Task (DDT) 45,46,54 and Balloon Analog Risk Task (BART). 45,49,58 Less commonly used tasks Probability Discounting Task (DPDT), 54 Immediate Memory/Delayed Memory Task, 46 Modified Progressive Ratio Task, 44 Matching Familiar Figures Test (MFFT), 51 4-Choice Serial Reaction Time Task (4CSRT), Beads Task (BT), 56 High Event Rate Vigilance Task (HERVT), 59 Conners' Continuous Performance Test (CCPT), 48 Iowa Gambling Task 48 and Wisconsin Card Sorting Test (WCST).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…These effects on delayed reward discounting seem partially dependent on interactions with the serotonergic system given that the effects of d-amphetamine are lost following depletion of brain serotonin levels (Winstanley et al, 2003). Human laboratory studies have proved more mixed, with some studies reporting similar effects of dopaminergic agents on measures of delay discounting depending on the analytic approach (e.g., de Wit, Enggasser, & Richards, 2002) whereas others have reported null results (Lile et al, 2011;Reed & Evans, 2016;Reed, Levin, & Evans, 2010). This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Neuroscience: Neurochemical Systems and Neuropharmacological...mentioning
confidence: 99%
“…Interestingly, the NRI atomoxetine has been found to inhibit cue‐induced cocaine self‐administration in mice . Three drug trials in human subjects have been conducted, all with a focus on improving impulsivity in cocaine users . Schmitz et al .…”
Section: Treatment Of Co‐occurring Impulsivity and Sudsmentioning
confidence: 99%
“…Another RCT compared modafinil with CBT to CBT alone in crack cocaine users and found no improvement in impulsivity measures . Finally, an open‐label trial was conducted with d ‐amphetamine in cocaine users, but they also found that the drug had no effect on impulsivity . No human studies have yet investigated the effects of NRIs in individuals with stimulant use disorders.…”
Section: Treatment Of Co‐occurring Impulsivity and Sudsmentioning
confidence: 99%